A monoclinic crystal form of casein kinase 1 δ. Issue 10 (8th October 2013) - Zeringo, Nicholas A.; Murphy, Lea; McCloskey, Eric A.; Rohal, Loren; Bellizzi, John J.
<x xml:space="preserve">Abstract</x> Casein kinase 1 δ (CK1δ) is a regulatory enzyme in the mammalian circadian oscillator and represents a potential pharmacological target for modulating circadian rhythms. Crystal structures of four different polymorphs of CK1δ have previously been determined and this article reports the crystallization and structure determination of a new crystal form belonging to space group P21. Comparison of CK1δ crystal structures reveals few conformational differences within the C‐terminal lobe, but more significant movements of the β‐sheet region of the N‐terminal lobe were observed.